Commentary on the portfolio of compositions - van Tonder, Cobi (Trinity College (Dublin, Ireland). Department of Music, 2016)
The portfolio contains seven compositions with varying instrumentation, ranging from string quartet to computer processed voice ensemble to purely electronic forces. Fata Morgana is the largest work in the portfolio and written for female voice ensemble, percussion and live computer processing or tape. Its main concern is that of extending the human voice via the auditory illusion of the Shepard’s tone. String Quartet No 1 contains excessive glissade to expose microtonal qualities. Haute Rorschach, When all memory is gone, Drift, Gala and Mutation 2 all explore complex and unique microtonal tuning systems and are written with instrumentation left relatively open ended: given certain conditions, both acoustic and electronic forces are able to perform it. The most prominent compositional aspect that features in the portfolio is an approach towards the experience of movement in terms of colour, form, texture and space. Material consists of lines and curves such as glissandi or the Shepard’s tone auditory illusion, pitch fields, waves, pulses, flickering morphologies, distorted glows, morphs and slow transformations. This material originates from focusing on the internal properties of sounds, for example, the use of microtonal intervals that are clustered to produce beating patterns, third tones and unique colors. Macro forms are determined by this material and range from drone to simplistic, repetitive gestures. The final approach is a focus on the experience of sound in and as space: most pieces feature artificial acoustics as prominent part of the material and overall texture.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin